Similarity Analysis and Design of Gear Transmission Systems - 周美立; 齐从谦; 吴天星 (Jixie chuandong)
In this paper,the recognition and expression of component elements of gear transmission systems,the construction method of similarity unit,the principle of similarity analysis and the design of similar systems,and a relationship between similarity measure and series design are studied.Also,an example to verify the practicability of the theory and method is given.